A Capture and Access Mechanism for Accurate Recording and Playing of 3D Virtual Environment Simulations - Boukerche, Azzedine; Lopes, Altieres Ribeiro; de Araujo, Regina Borges (2006 Tenth IEEE International Symposium on Distributed Simulation and Real-Time Applications, 2006)
3D virtual environments (3DVEs), wireless sensor networks and context aware computing can be integrated for accurate monitoring of physical environments subject to emergency situations. Events that are captured from the physical world, through wireless sensor networks, can be recorded as they occur and visualized in either real-time or at posteriori. Recording and playing 3DVEs can overcome the limitations of hypermedia interfaces or continuous media when the experiences of the real world are very complex. This paper describes the design, implementation and evaluation of a 3D media recording and playing system, which allows users to play live experiences captured from the physical world for analysis, evaluation, monitoring and training. The novelty of this system resides in two aspects: it uses an optimized recording technique that saves processing time and storage space; it records scene updating commands independent from the 3D Player being used. The optimized mechanism was compared against other existing mechanisms. The results show a better performance for the class of applications that have arbitrary and large number of events generated at any moment, as is the case of emergency preparedness applications.